Redox‐controlled preservation of organic matter during "OAE 3" within the Western Interior Seaway. (16th June 2015) - Tessin, Allyson; Hendy, Ingrid; Sheldon, Nathan; Sageman, Bradley
Abstract: During the Cretaceous, widespread black shale deposition occurred during a series of Oceanic Anoxic Events (OAEs). Multiple processes are known to control the deposition of marine black shales, including changes in primary productivity, organic matter preservation, and dilution. OAEs offer an opportunity to evaluate the relative roles of these forcing factors. The youngest of these events—the Coniacian to Santonian OAE 3—resulted in a prolonged organic carbon burial event in shallow and restricted marine environments including the Western Interior Seaway. New high‐resolution isotope, organic, and trace metal records from the latest Turonian to early Santonian Niobrara Formation are used to characterize the amount and composition of organic matter preserved, as well as the geochemical conditions under which it accumulated. Redox sensitive metals (Mo, Mn, and Re) indicate a gradual drawdown of oxygen leading into the abrupt onset of organic carbon‐rich (up to 8%) deposition. High Hydrogen Indices (HI) and organic carbon to total nitrogen ratios (C:N) demonstrate that the elemental composition of preserved marine organic matter is distinct under different redox conditions. Local changes in δ 13 C indicate that redox‐controlled early diagenesis can also significantly alter δ 13 Corg records. These results demonstrate that the development of anoxia is of primary importance in triggering the prolonged carbon burial in the Niobrara Formation. Sea level reconstructions, δ 18 O results, and Mo/total organic carbon ratios suggest that stratification and enhanced bottom water restriction caused the drawdown of bottom water oxygen. Increased nutrients from benthic regeneration and/or continental runoff may have sustained primary productivity. Key Points: Bottom water redox changes triggered carbon burial within the WIS during OAE 3 Anoxia developed due to O2 drawdown in a stratified water column Redox‐controlled changes in OM preservation altered primary δ 13 Corg signals